WORKFORCE REGIONAL DISPARITIES FROM THE RURAL AREA IN ROMANIA - ANDREI, Madalina-Teodora; POP, Iuliana; GHIC, Grațiela (Annals of Spiru Haret University. Economic Series, 2018)
The beginning of the third millennium has brought up in Romania significant changes as far as the demographic and economic phenomena in general, and the workforce from the rural area in particular. The demographic evolution in Romania is influenced by multiple factors, including economic, social and political ones. This article aims at performing a quantitative analysis on the employment level and development trends of Romania’s rural area population at the regional level with a view of becoming competitive at the European level.